TWO WEST AFRICAN MOLLUSCAN SPECIES (GASTROPODA, ACTEONIDAE) FROM MIS 5.5 IN THE TARANTO AREA (SOUTHERN ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
Two gastropods of the family Acteonidae, Acteon senegalensis (Petit de la Saussaye, 1851) and Acteon maltzani Dautzenberg, 1910, are reported for the first time from shallow-water deposits of the Last Interglacial (MIS 5.5) cropping out in the Taranto area (Southern Italy). Both species inhabit the coast of West Africa, and their presence in the MIS 5.5 deposits is attributable to the northward flow of tropical species, referred to in the literature as Senegalese Guests. The two species exhibit non-planktotrophic larval development, confirming that species without a long planktonic life stage can spread effectively in response to climate change.
Keywords: Acteon senegalensis; Acteon maltzani; Last Interglacial; Senegalese Guests; Apulia.